GOVERNMENT-OWNED ENTERPRISES (GOEs) IN INDONESIA’S COMPETITION LAW AND PRACTICE - Arie Siswanto; Marihot Janpieter Hutajulu (Yustisia, 2019)
In the competition law discourse, one of the controversial issues is the position of Government-Owned Enterprises (GOEs). There are basically two main views regarding the status of GOEs in the competition law. First, GOEs should be granted privileges, even excluded from the scope of business competition law. Secondly, since GOEs are basically businesses and competitors to private enterprises, GOEs must also be subject to competition law. This paper discusses the status of GOEs in Indonesia’s competition law, both in the context of normative framework and in the implementation of competition law provisions. For this purpose, this paper examine the rules of competition law governing the GOEs and analyze some cases of alleged violations of competition law examined by the KPPU as the Indonesian competition authority. This study found that basically Indonesia’s competition law follows the so-called “competitive neutrality” principle in which the law treat both GOEs and private enterprises in equal manner. However, at the practical domain, the cases studied indicates that monopolistic or dominant position held by GOEs may be abused to favor subsidiaries which are in direct, head to head competition, with private enterprises.